2008
DOI: 10.1038/leu.2008.49
|View full text |Cite
|
Sign up to set email alerts
|

The immunophenotype of different immature, myeloid and B-cell lineage-committed CD34+ hematopoietic cells allows discrimination between normal/reactive and myelodysplastic syndrome precursors

Abstract: Occurrence of phenotypic abnormalities in CD34þ hematopoietic progenitor and precursor cells (HPC) and their major B-cell and nonlymphoid compartments has been frequently reported in myelodysplastic syndromes (MDS). Here, we analyze for the first time the numerical and phenotypic abnormalities of different maturation-associated subsets of bone marrow (BM) CD34þ HPC from 50 newly diagnosed MDS patients in comparison to normal/reactive BM (n ¼ 29). Our results confirm the existence of heterogeneously altered phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
137
0
13

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(181 citation statements)
references
References 37 publications
17
137
0
13
Order By: Relevance
“…As already described by several reports [11][12][13][14], one finding emerging from our study concerned precursor B cells, not detectable in the majority (70%) of MDS patients. Furthermore, several alterations emerged in MDS within CD34þ and mature compartments.…”
Section: Phenotypic Analysis Of Mds Compared To Controlssupporting
confidence: 66%
See 2 more Smart Citations
“…As already described by several reports [11][12][13][14], one finding emerging from our study concerned precursor B cells, not detectable in the majority (70%) of MDS patients. Furthermore, several alterations emerged in MDS within CD34þ and mature compartments.…”
Section: Phenotypic Analysis Of Mds Compared To Controlssupporting
confidence: 66%
“…Our approach was adapted from the one described by Matarraz et al [13]. Briefly, some major BM cell compartments were identified on the basis of forward (FSC) and sideward (SSC) light scatter characteristics and their reactivity for CD45 and CD34 ( Figs 1A,B,D,E,G,H).…”
Section: Distinctive Phenotype Of Pnh Bone Marrow Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore addressed whether pDC CD34 þ precursors coexpress NG2. Interestingly, we found that 12.2% of the pDC precursors (CD34 þ /CD45 þ /CD38 þ / CD123 high /HLADR þ ) [65][66][67] readily coexpress NG2 (Figure 2c). This suggests that, regardless of the status of the MLL locus, the NG2 antigen may be expressed in pDC leukemias if the leukomogenesis process is initially triggered in a pDC CD34 þ precursor readily expressing NG2, which might act as a leukemic-initiating cell.…”
Section: Environmental Exposures and Delayed Infection Early In Life mentioning
confidence: 96%
“…Hierarchical clustering of flow cytometry data with different subsets of hematopoietic progenitor and precursor cells allowed discrimination of cases with normal bone marrow from MDS RAEB-2 in all cases, and a predictive lower value was obtained for the separation of patients with MDS subtypes RA, RCMD, or MDS RAEB-1 from cases with normal bone marrow. 35 Furthermore, clonal chromosomal aberrations were detected in 14.3% in the group being classified as MDS by flow cytometry, whereas cytomorphology produced no suspicion of MDS. Therefore, it was demonstrated that immunophenotyping could diagnose MDS in some cases that were not detectable by cytomorphological criteria.…”
Section: Diagnostic Workup Of Mds/bacher Et Almentioning
confidence: 99%